DISTRICT HEAD'S LEADERSHIP STYLE ENHANCES CIVIL SERVANTS' MOTIVATION FOR ACHIEVING GOOD GOVERNANCE IN NORTH SORONG - Reinhart R.P. Andilolo; Watunglawar, Balthasar; Hafel , Muhlis (Moestopo International Review on Social, Humanities, and Sciences, 2024)
The leadership role at the district level plays a crucial part in promoting good governance, particularly in Sorong Utara District, part of Sorong City in Southwest Papua Province. This study focuses on transformational leadership and its impact on fostering motivation among civil servants within a supportive work environment. Using a descriptive-analytical method, the research aims to explore how leadership practices such as empathy, strategy development, guidance, integrity, and transparency influence civil servant motivation in achieving good governance. Findings reveal several challenges for leadership, particularly in upholding discipline, professionalism, and showing empathy towards employees' rights. Effective leadership strategies are required for developing guidance, enhancing integrity, and maintaining transparency, all of which are critical for boosting civil servant motivation. The study highlights that leaders who provide motivation, promote career development, and enable better public service delivery have a significant influence on staff performance. The research also establishes a positive link between civil servant motivation and improved performance. Motivational interventions that focus on optimizing the relationship between employees and their work environment can enhance both productivity and well-being. Ultimately, leaders who prioritize integrity, fairness, and the public interest over personal agendas can inspire staff to achieve organizational goals and help realize good governance.